Expanding the Supply of Pasteurized Donor Milk: Understanding Why Peer-to-Peer Milk Sharers in the United States Do Not Donate to Milk Banks. (May 2016) - Perrin, Maryanne Tigchelaar; Goodell, L. Suzanne; Fogleman, April; Pettus, Hannah; Bodenheimer, Amanda L.; Palmquist, Aunchalee E. L.
Background: Lactating women in the United States have several options for what they do with excess breast milk, including donating to milk banks that serve medically fragile infants, sharing directly with families seeking milk, and selling to individuals or for-profit entities. The World Health Organization and the US Surgeon General have issued calls to increase access to pasteurized donor milk for medically fragile infants. Objective: To explore how lactating women with a surplus of breast milk come to the decision to share their milk with a peer rather than donate to a milk bank. Methods: A qualitative design using a grounded theory approach was employed. Semistructured telephone interviews were conducted with 27 women who had shared milk with a peer but not with a milk bank. Results: Five dominant themes were identified: a strong belief in the value of breast milk, unexpected versus planned donation, sources of information regarding milk exchange, concerns and knowledge gaps about milk banks, and helping and connecting. Conclusions: This research offers insights into potential strategies for promoting milk bank donation among peer-to-peer milk sharers, including developing donor education campaigns focused on knowledge gaps regarding milk banks and developing health care professional referral programs that can reduce barriers associated with the convenience of milk bank donation.